2016
DOI: 10.5037/jomr.2016.7103
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Radiographic, and Histologic Evaluation of Maxillary Sinus Lift Procedure Using a Highly Purified Xenogenic Graft (Laddec®)

Abstract: ObjectivesThe aim of this study was to evaluate the clinical, radiographic and histologic results when a highly purified xenogenic bone (Laddec®) was used as grafting material in maxillary sinuses.Material and MethodsIn fifteen patients requiring unilateral maxillary sinus augmentation, the grafting procedure was performed with Laddec®. Forty-two implants were installed after a 6 month healing period. The height of the augmented sinus was measured radiographically immediately after augmentation and postoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 34 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…Some bone substitute materials, such as HA, β-TCP, and xenogeneic grafts, are being currently used clinically. [1][2][3][4]40 However, they are not permitted for bone augmentation in dental implant treatment or alveolar defect according to Japan's Pharmaceutical Affairs Law. Moreover, the purpose of this study was to prove that the effectiveness was non-inferior in comparison with autologous bone or other materials for the approval of OCP/Col; this clinical trial was designed as a single-arm study because no approved material for dental implant treatment was available during the trial in Japan and autologous bone was associated with secondary invasion and infection risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some bone substitute materials, such as HA, β-TCP, and xenogeneic grafts, are being currently used clinically. [1][2][3][4]40 However, they are not permitted for bone augmentation in dental implant treatment or alveolar defect according to Japan's Pharmaceutical Affairs Law. Moreover, the purpose of this study was to prove that the effectiveness was non-inferior in comparison with autologous bone or other materials for the approval of OCP/Col; this clinical trial was designed as a single-arm study because no approved material for dental implant treatment was available during the trial in Japan and autologous bone was associated with secondary invasion and infection risk.…”
Section: Discussionmentioning
confidence: 99%
“…In oral and maxillofacial, orthopedic, and plastic surgeries, it is important to restore shape and function by augmenting bone for congenital bone defects or those acquired by injury. Hydroxyapatite (HA), 1 β-tricalcium phosphate (β-TCP), 2,3 and xenogeneic grafts, such as bovine bone, 4 have been clinically used as bone substitutes. Although these materials have osteoconductive properties and are effective for filling bone defects, their ability of bone formation may be insufficient in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is abundantly available, it does not have the high osteoconductivity seen with autografts [ 14 ]. Hydroxyapatite (HA) [ 15 ], β-tricalcium phosphate (β-TCP) [ 16 ], and xenogenic grafts, such as bovine bone [ 17 ], have been used clinically as bone substitutes. These materials have efficacy for titanium dental implantation and show good osseointegration [ 15 , 18 , 19 ], although they are inferior to autologous bone in these respects.…”
Section: Introductionmentioning
confidence: 99%
“…The three major mechanisms that are required to repair osseous defects are (i) osteoconduction, (ii) osteoinduction, and (iii) osteogenesis. 2,29 Previous literature has demonstrated that xenografts support bone regeneration through osteoconduction, and have been applied to repair bony defects 11 and maxillary sinus lift procedures 30 with positive results.…”
Section: Discussionmentioning
confidence: 99%
“…The three major mechanisms that are required to repair osseous defects are (i) osteoconduction, (ii) osteoinduction, and (iii) osteogenesis 2,29 . Previous literature has demonstrated that xenografts support bone regeneration through osteoconduction, and have been applied to repair bony defects 11 and maxillary sinus lift procedures 30 with positive results. In the present study, two unsintered grafting materials, DBBL and DBBB, were utilized for the regeneration of 8 mm sized defects in rabbits' calvaria, which were evaluated by histological and histomorphometrical analyses, 31,32 and compared to a non‐grafted defect that was used as a negative control.…”
Section: Discussionmentioning
confidence: 99%